Role of endothelium-derived relaxing factor in renal autoregulation in conscious dogs - Baumann, J. Ê.; Persson, Pontus B.; Ehmke, Heimo; Nafz, Benno; Kirchheim, Hartmut (American journal of physiology. Renal physiology, 1992)
In six chronically instrumented, conscious dogs the hypothesis was tested that the release of endothelium-derived relaxing factor (EDRF) is important for autoregulation of renal blood flow (RBF) and glomerular filtration rate (GFR). RBF was measured by a Transonic flowmeter. Renal perfusion pressure was servo-controlled by an aortic cuff. EDRF synthesis was inhibited by NG-nitro-L-arginine methyl ester (L-NAME, 50 mg/kg iv). L-NAME increased mean systemic blood pressure (30 mmHg) and decreased heart rate (-40 beats/min), but it left autoregulation of RBF and GFR intact. However, basal RBF decreased markedly (2.24 +/- 0.32 ml.min-1.g-1 with L-NAME vs. 3.91 +/- 0.64 ml.min-1.g-1 for control, P less than 0.01), whereas basal GFR was not significantly influenced (0.37 +/- 0.05 ml.min-1.g-1 with L-NAME vs. 0.42 +/- 0.06 ml.min-1.g-1 for control). Hence filtration fraction increased with L-NAME [27.6 +/- 1.7% vs. 19.3 +/- 1.3% (P less than 0.01)]. The lower limit of autoregulation remained unchanged for RBF (64 +/- 5 mmHg with L-NAME vs. 63 +/- 3 mmHg for control) and increased slightly for GFR (74 +/- 2 mmHg with L-NAME vs. 67 +/- 1 mmHg for control, P less than 0.01). In conclusion, basal EDRF activity tonically influences renal resistance vessels; however, EDRF release is not primarily involved in the process of renal autoregulation. The maintenance of GFR suggests that this effect is localized in preglomerular as well as in postglomerular arterioles.